A case of silent myocardial ischemia associated with severe and prolonged hypoglycemia - Antonio Villa1; Donata Saltafossi2; Annalisa Re1; Silvia Garavaglia1 (Journal of Health and Social Sciences)
The scientific literature on treatment options and complications following large insulin overdoses is limited to case reports and few retrospective, epidemiological reports providing limited clinical insights. The effect of hypoglycemia on the heart is uncertain. There are two main factors that are commonly associated with electrocardiographic changes during hypoglycemia, of which the first is linked to the rapid decrease in blood glucose levels, and the other to the decrease in potassium serum levels. We report a case of severe and prolonged hypoglycemia due to deliberate misuse of long-acting insulin associated with transient electrocardiographic ischemic changes without symptoms of myocardial ischemia. We diagnosed and treated this patient as a case of silent cardiac ischemia. Hypoglycemia is a common event in patients affected by insulin dependent diabetes mellitus. The emergency physicians should be aware of aspecific or ischemic ECG alterations associated with severe hypoglycemia. As shown in this case report, ECG monitoring is crucial for early detection of ischemic electrocardiographic changes suggestive of myocardial ischemia in diabetic patients.